Imaging markers of small vessel disease and brain frailty, and outcomes in acute stroke. (4th February 2020) - Appleton, Jason P.; Woodhouse, Lisa J.; Adami, Alessandro; Becker, Jennifer L.; Berge, Eivind; Cala, Lesley A.; Casado, Ana M.; Caso, Valeria; Christensen, Hanne K.; Dineen, Robert A.; Gommans, John; Koumellis, Panos; et al.
Abstract : Objective: To assess the association of baseline imaging markers of cerebral small vessel disease (SVD) and brain frailty with clinical outcome after acute stroke in the Efficacy of Nitric Oxide in Stroke (ENOS) trial. Methods: ENOS randomized 4, 011 patients with acute stroke (<48 hours of onset) to transdermal glyceryl trinitrate (GTN) or no GTN for 7 days. The primary outcome was functional outcome (modified Rankin Scale [mRS] score) at day 90. Cognition was assessed via telephone at day 90. Stroke syndrome was classified with the Oxfordshire Community Stroke Project classification. Brain imaging was adjudicated masked to clinical information and treatment and assessed SVD (leukoaraiosis, old lacunar infarcts/lacunes, atrophy) and brain frailty (leukoaraiosis, atrophy, old vascular lesions/infarcts). Analyses used ordinal logistic regression adjusted for prognostic variables. Results: In all participants and those with lacunar syndrome (LACS; 1, 397, 34.8%), baseline CT imaging features of SVD and brain frailty were common and independently associated with unfavorable shifts in mRS score at day 90 (all participants: SVD score odds ratio [OR] 1.15, 95% confidence interval [CI] 1.07–1.24; brain frailty score OR 1.25, 95% CI 1.17–1.34; those with LACS: SVD score OR 1.30, 95% CI 1.15–1.47, brain frailty score OR 1.28, 95% CI 1.14–1.44). Brain frailty was associated with worse cognitive scores at 90 days in all participants and in those with LACS. Conclusions: Baseline imaging features of SVD and brain frailty were common in lacunar stroke and all stroke, predicted worse prognosis after all acute stroke with a stronger effect in lacunar stroke, and may aid future clinical decision-making. Identifier: ISRCTN99414122.